COMPUTING EXPERIMENT FOR ASSESSMENT OF AERODYNAMIC CHARACTERISTICS OF SEPARATE ELEMENTS IN THE STRUCTURE OF THE FUSELAGE OF A HELICOPTER - V. A. Ivchin; V. G. Sudakov; A. A. Ryzhov (Научный вестник МГТУ ГА, 2016)
The present publication describes the calculation of helicopter fuselage aerodynamic characteristics and its separate elements, by computing experiment. On the basis of program commercial package CFX ANSYS the technique has been mastered and longitudinal and lateral characteristics of the helicopter fuselage on the various flight modes are calculated.